Nectar bacteria, but not yeast, weaken a plant-pollinator mutualism - Vannette, Rachel L; Gauthier, Marie-Pierre L; Fukami, Tadashi (Proceedings of the Royal Society. B, Biological sciences, 2013)
Mutualistic interactions are often subject to exploitation by species that are not directly involved in the mutualism. Understanding which organisms act as such 'third-party' species and how they do so is a major challenge in the current study of mutualistic interactions. Here, we show that even species that appear ecologically similar can have contrasting effects as third-party species. We experimentally compared the effects of nectar-inhabiting bacteria and yeasts on the strength of a mutualism between a hummingbird-pollinated shrub, Mimulus aurantiacus, and its pollinators. We found that the common bacterium Gluconobacter sp., but not the common yeast Metschnikowia reukaufii, reduced pollination success, seed set and nectar consumption by pollinators, thereby weakening the plant-pollinator mutualism. We also found that the bacteria reduced nectar pH and total sugar concentration more greatly than the yeasts did and that the bacteria decreased glucose concentration and increased fructose concentration whereas the yeasts affected neither. These distinct changes to nectar chemistry may underlie the microbes' contrasting effects on the mutualism. Our results suggest that it is necessary to understand the determinants of microbial species composition in nectar and their differential modification of floral rewards to explain the mutual benefits that plants and pollinators gain from each other.